Individualized autoregulation-guided arterial blood pressure management in neurocritical care - Jonathan R. Gomez; Bhagyashri U. Bhende; Rohan Mathur; L. Fernando Gonzalez; Vishank A. Shah (Neurotherapeutics)
Cerebral autoregulation (CA) is the physiological process by which cerebral blood flow is maintained during fluctuations in arterial blood pressure (ABP). There are various validated methods to measure CA, either invasively, with intracranial pressure or brain tissue oxygenation monitors, or noninvasively, with transcranial Doppler ultrasound or near-infrared spectroscopy. Utilizing these monitors, researchers have been able to discern CA patterns in several pathological states, such as but not limited to acute ischemic stroke, spontaneous intracranial hemorrhage, aneurysmal subarachnoid hemorrhage, sepsis, and post-cardiac arrest, and they have found CA to be altered in these patients. CA disturbances predispose patients suffering from these ailments to worse outcomes. Much focus has been placed on CA monitoring in these populations, with an emphasis on arterial blood pressure optimization. Many guidelines recommend universal static ABP targets; however, in patients with altered CA, these targets may make them susceptible to hypoperfusion and further neurological injury. Based on this observation, there has been much investigation on individualized ABP goals and their effect on clinical outcomes. The scope of this review includes (1) a summary of the physiology of CA in healthy adults; (2) a review of the evidence on CA monitoring in healthy individuals; (3) a summary of CA changes and its effect on outcomes in various diseased states including acute ischemic stroke, spontaneous intracranial hemorrhage, aneurysmal subarachnoid hemorrhage, sepsis and meningitis, post-cardiac arrest, hypoxic-ischemic encephalopathy, surgery, and moyamoya disease; and (4) a review of the current evidence on individualized ABP changes in various patient populations.